KARAKTERISTIK FISIK, GEOKIMIA DAN SEBARAN ENDAPAN NIKEL LATERIT DAERAH LOJI BEACH, PULAU OBI, KABUPATEN HALMAHERA SELATAN, PROVINSI MALUKU UTARA: PHYSICAL, GEOCHEMICAL CHARACTERISTICS AND DISTRIBUTION OF NICKEL LATERITE DEPOSITS IN THE LOJI BEACH AREA, OBI ISLAND, SOUTH HALMAHERA DISTRICT, NORTH MALUKU PROVINCE - Trisusanti, Eliana; Patonah, Aton; Hardiyono, Adi; Matano, Alan (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2025)
Indonesia is one of the largest nickel producing countries in the world. One of the nickel producing areas in Indonesia is in the Loji Beach area. This research area is located on Obi Island, South Halmahera Regency, North Maluku Province. Geologically, the research area is composed of ultramafic rocks. This research aims to determine the characteristics of nickel laterite and its relationship with geological conditions in the research area using petrographic methods of rock samples and XRF (X-Ray Fluorescence) geochemistry of drilling samples. Geochemical data in the form of Ni content from drill data was interpolated using the IDW method using ArcGIS software. Based on research results, Ni-laterite is abundant in the morphology of gentle hills with a slope of 0-7%. The base rock bearing Ni-laterite is thought to be serpentinite from the serpentinization of harzburgite and dunite. Based on petrographic analysis, the bedrock is composed of >85% serpentine, the rest is relict minerals olivine and orthopyroxene, as well as other minerals such as talc, oxide minerals and opaque. The results of geochemical analysis show that in the limonite zone there is an abundance of Fe elements, while in the saprolite zone the Ni element is enriched with levels of 1.5% -2.8%.